PENINGKATAN KETERAMPILAN SOSIAL ANAK USIA DINI MELALUI PERMAINAN TRADISIONAL BABANCAKAN DI POS PAUD MELATI O3 - Handayani, Ambara Sri (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
This research raises the problem of: Early Childhood Education Teacher Education Study Program titled "Improving Early Childhood Social Skills Through Traditional Games Babancakan At Pos Paud Melati O3" .The goal to be achieved through this research is to know and describe: In general, research aims to "To know the description of objective conditions of social intelligence in POS PAUD Melati 03. To know the process of implementation of traditional games in POS PAUD Melati 03 to improve and motivate the child in improving social skills.To know the results of traditional games in order to improve the social skills of children early age in POS PAUD Melati 03 ". This research is carried out with the approach used in this research is qualitative research approach. Sugiyono (2009: 21-22). The source of this research data is the child of World Kid Students Cimahi. While the sample amounted to 30 children as well as used as a sample refresentatif are 2 teachers and 5 children to be a case. The research data was collected by using instrument in the form of interview guide and observation guideline. The use of traditional games to improve children's social intelligence in this study was conducted through two observations. From the results of observations that have been done there is a fairly good improvement on the development of social skills of children in every action on each activity. The results of observations from the improvement of the development of Child Social Skills are seen by comparing the results of each assessment indicator achieved either by the child on the initial observation with the results of each activity. Increases not only occur in every assessment indicator, but every child in POS PAUD Melati 03